Effects of augmented feedback on landing force from jumps - Mahmod Abdul Kadir, Low Jeffrey Fook Lee, (Universiti Pendidikan Sultan Idris, 2017)
Effects of augmented feedback on landing force from jumps by Mahmod Abdul Kadir, Low Jeffrey Fook Lee,